1. The problem statement, all variables and given/known data https://webwork.utpa.edu/webwork2_files/tmp/equations/2d/02a7e6a06f5b2424758fa01cc965f71.png [Broken] with https://webwork.utpa.edu/webwork2_files/tmp/equations/80/81c176aa8964438a63eb096513245f1.png [Broken] 2. Relevant equations Standard form: y' + p(x)y = f(x) Integrating factor: r(x)= e∫p(x)dx Solution: y(x) = e-∫p(x)dx(∫e∫p(x)dx ⋅ f(x) dx + C) 3. The attempt at a solution From, y' - y = 7et + 56e8t I got, p(x) = -1 and f(x) = 7et + 56e8t So the integrating factor is r(t)= e∫-1 dt = e-t Plug it into the solution formula, y(t)= et [∫e-t (7et + 56e8t) dt + C] = et (7t + 8e7t+ C) = 7tet + 8e8t+ Cet Using the initial condition y(0)= 2 = 8 + C = 2 C = -6 My final solution, y(t) = 7tet + 8e8t- 6et check: y(0) = 7(0)e(0) + 8e8(0)- 6e(0) = 2 But when I type it into WeBWork, it says my answer is incorrect. I don't think its a syntax problem because it has a preview button that allows you to see your actual problem. Could it be that, y' - y = 7et + 56e8t is not in standard form?